1978
DOI: 10.1111/j.1468-2958.1978.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Silence Isn't Necessarily Golden: Communication Apprehension, Desired Social Choice, and Academic Success Among Middle-School Students

Abstract: Communication apprehension was found to be significantly negatively related to both middle-school students' attitudes toward school and final grades. In addition, communication apprehension was found to influence the choice of desired others made by students and their teacher in a classroom communication network. In general, communication apprehensive students were found not to be considered desirable communication choices by their peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…Finally, previous research reported that students' trait CA predicted attitudes toward school in general (Hurt & Preiss, 1978). Perhaps trait CA is negatively associated with generalized or traitlike attitudes toward school, but this investigation found no such relationship for specific attitudes toward a class.…”
Section: Discussioncontrasting
confidence: 42%
“…Finally, previous research reported that students' trait CA predicted attitudes toward school in general (Hurt & Preiss, 1978). Perhaps trait CA is negatively associated with generalized or traitlike attitudes toward school, but this investigation found no such relationship for specific attitudes toward a class.…”
Section: Discussioncontrasting
confidence: 42%
“…High apprehensives score lower on their SAT scores than low apprehensives and have lower grade point averages (McCroskey & Andersen, 1976), and lower grades in the basic course and on performance assignments (Powers & Smythe, 1980). High apprehensives have more negative attitudes towards school and their final grades (Hurt & Preiss, 1978). Both teachers (Smythe & Powers, 1978) and peers (Hurt & Preiss, 1978) develop negative perceptions about high apprehensives' potential for academic and social success.…”
mentioning
confidence: 93%
“…High apprehensives have more negative attitudes towards school and their final grades (Hurt & Preiss, 1978). Both teachers (Smythe & Powers, 1978) and peers (Hurt & Preiss, 1978) develop negative perceptions about high apprehensives' potential for academic and social success.…”
mentioning
confidence: 97%
“…scores than either moderate or high apprehensives, 55 while CA was negatively correlated to junior high students' attitudes toward school and final grades. 56 Finally, an hypothesized relationship was not found between community size and a person's level of CA. 57 A second set of studies included five articles examining the relationship between college student CA and achievement.…”
Section: Student Characteristicsmentioning
confidence: 96%